Clinical Applications of Cardiac CT - Cademartiri, Filippo; Casolo, Giancarlo; Midiri, Massimo (Springer Milan, 2012)
During the past few years, cardiac CT (CCT) has acquired an increasingly important role as a noninvasive imaging method that allows assessment of coronary heart disease from both the morphological and the functional standpoint. It is quickly becoming a primary clinical tool for the evaluation and follow-up of various conditions related to the heart and great vessels and is providing valuable insights into the natural history of atherosclerosis. The rapid advances in CCT technology, the advent of new clinical applications, and the acquisition of data on prognostic value are just some of the reasons for the publication of this new edition of Clinical Applications of Cardiac CT, little more than 3 years after the first edition appeared. The text has been extensively revised and updated to reflect current knowledge and practice, and the structure and layout of the educational content have also been improved. The imaging targets, semeiology, technique, and clinical applications of CCT are all covered in detail, and in addition relevant information is provided on epidemiology, clinical assessment, and the role of other diagnostic modalities. This book will prove an invaluable tool for radiologists and cardiologists alike